A Review of Leadership Theories in Healthcare - Farha Rizwan Sikalgar; Deepak Bangera; Manasvi P Kumar; Bhuvaneshwari; Yuvaraj Paul; Shrikanth Muralidharan (Journal of Pharmacy and Bioallied Sciences)
Leadership plays a critical role in shaping the dynamics, quality, and outcomes of healthcare systems. This review explores the evolution and application of leadership theories within the healthcare sector, highlighting their relevance in addressing complex organizational challenges. Key theories, including transformational, transactional, servant, and situational leadership, are analyzed for their impact on team performance, patient outcomes, and organizational efficiency. Emphasis is placed on the importance of adaptive and inclusive leadership approaches in responding to the rapidly changing healthcare landscape. The review also examines the interplay between leadership styles and factors such as staff morale, interprofessional collaboration, and innovation. By synthesizing theoretical insights and practical applications, this review provides a comprehensive understanding of how leadership theories can guide effective management and improve healthcare delivery.